Analisis Kreativitas Guru dalam Meningkatkan Keterampilan Berbahasa di Kelas V UPT SDN 290 Gresik - Mumtazah, Dzakiyatul; Siswoyo, Andika Adinanda (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to describe how students' language skills are in Indonesian language subjects and to find out how creativity is carried out by teachers in improving students' language skills in Indonesian language subjects in class V UPT SDN 290 Gresik. This research uses qualitative methods with a field research model. Researchers must go directly into the field to obtain information through qualitative methods, namely the researcher's role as a key instrument. This type of descriptive qualitative research is used by researchers to provide an overview of the research conducted through interviews, observations, questionnaires, and documentation. The results of the research conducted show that there are some students who have not fully mastered language skills, but teachers try to awaken their teaching creativity to be able to overcome these problems. Based on the results of observations, it is said that the teacher's creativity is in the very good category. This is also supported by the results of the observation sheet which obtained a total score of 486 with a percentage of 78.73% and a score of 66-79 meaning it is in the good category